Accuracy of nuchal translucency measurement depends on equipment used and its calibration. (July 2014) - Axell, R. G.; Gillett, A.; Pasupathy, D.; Chudleigh, T.; Brockelsby, J.; White, P. A.; Lees, C. C.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 6–7